Какая система формирования парламента подходит для Украины - Школьников, А. (Социология: теория, методы, маркетинг, 2000)
Efficient work of the higher government legislative body depends on optimum system of parliament formation with due regard of the world experience related to the specific features of the certain country. Taking into account the combined majority and proportional electoral system adopted in Ukraine in 1997, an actual problem is to analyze bad and good points of each of its components, to find the best their correlation under conditions of social transformations, unformed civil society institutions, lack of political stability.